Molecular Detecting of fungi and Bacteria in the ‎Blood of Patients With Genital System ‎Inflammatory Infection (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
A PCR technique was used to detect fungi and bacteria in the blood of patients with inflammatory infection of genital system, three primer sets were used to detect E. Coli , Candida spp. and existence of other fungi  The results showed infection by both microorganisms. All patients had bacteria in the blood stream while 30 % of them had a Candida spp. and the same percentage of other fungi species in blood